Aseptic Vertebral Body Necrosis in Unstable Traumatic Injuries of the Thoracolumbar Spine - Oleksii S. Nekhlopochyn; Vadim V. Verbov; Ievgen V. Cheshuk; Milan V. Vorodi (Ukrainian Neurosurgical Journal)
Instability from traumatic spinal injuries is a major indication for urgent stabilizing surgery to prevent adverse consequences of pathological mobility in the injured spinal segment. However, the staged evacuation of injured individuals from active combat zones and the need for urgent life-saving interventions often delay stabilization, leading to an increase in cases of delayed stabilization for unstable spinal injuries. Clinical analysis of such cases has revealed specific features that are underrepresented in the literature. One of these is post-traumatic aseptic necrosis in unstable injuries, which differs in several respects from Kummel disease and requires detailed characterization. Objective: To characterize and conduct a preliminary analysis of clinical cases of post-traumatic aseptic necrosis of the vertebral body in unstable thoracolumbar spinal injuries. Materials and Methods: A retrospective analysis was conducted on a patient database of those receiving inpatient treatment at the Romodanov Neurosurgery Institute of National Academy of Medical Sciences of Ukraine, between 2021 and 2024, as well as patients consulted in Kyiv healthcare institutions, either in person or via telemedicine. The primary inclusion criterion was a verified unstable traumatic injury of the thoracolumbar spine, where surgical stabilization was not performed within two weeks post-injury. Results: Nineteen cases of delayed stabilization for unstable thoracolumbar injuries were identified through medical documentation and imaging data. Six (31.6%) of these cases exhibited signs of aseptic post-traumatic vertebral necrosis. Clinical examples of patients with and without developed spondylonecrosis are presented. The groups were compared based on demographic and trauma-specific characteristics; however, statistically significant predictors for spondylonecrosis development were not identified. Additionally, the presence of chronic septic processes was not found to contribute to this phenomenon. Follow-up data indicated that delayed stabilization contributed to halting bone tissue lysis. Relevant literature on spondylonecrosis and a cascade of pathological processes potentially leading to this condition are discussed. Conclusions: This publication is among the first to describe post-traumatic aseptic vertebral body necrosis in unstable thoracolumbar spinal injuries. The data and proposed pathogenic mechanisms emphasize the importance of early stabilization for unstable injuries from both neurological and orthopedic perspectives.